Flora vascular dos campos rupestres: composição florística, esforço amostral e riqueza de espécies - Oliveira, Lilian Flavia Araujo (2017)
Campos Rupestres are a azonal vegetation formed by phytophysiognomies predominantly herbaceous-shrub, prone to fire, including campos limpos, campos sujos, swamps, gallery forests, bushlands, cerrado rupestre and rock outcrops. Due to the absence of an objectively delimited area, the floristic analyzes of Campos Rupestres richness were limited to regional floras until now. The use of shared databases available online can provide important information to indicate the state of knowledge about biodiversity, guiding future collection and research efforts, as well as to establish priority areas for conservation. This paper aimed to accomplish the first survey on the flora of vascular plants of Campos Rupestres sensu lato and to evaluate the spatial distribution of the sample effort and the species richness. For the analyzes, a database was used with records of vascular plants from the online platform of INCT - Virtual Herbarium of Flora and Fungi, occurring within a modeled area of potential distribution of the Campos Rupestres. A total of 159,260 records were analyzed, corresponding to 9,429 species, being 9,125 Angiosperms, 280 Monilophytes, 64 Lycophytes and 4 Gymnosperms, belonging to 200 families and 1,427 genera. Regarding to the endemic species of Campos Rupestres, we found a total of 1,494 species. The average collection density per km² in the Campos Rupestres was 2.4, below the ideal rate of 3 collections per km², and it indicates the need for more collection efforts in 68% of the analyzed squares. Species richness was significantly correlated with the number of records. Strategies such as digitization efforts of herbarium specimens, data processing by specialists, formation of new taxonomists, and the intensification of collection efforts, especially in areas of high diversity and low collection density, are essential for quantitatively and qualitatively improving data available on the flora of the Campos Rupestres. The Campos Rupestres as a whole should be considered as a priority for conservation, since they represent 28% of the vascular flora of Brazil in an area corresponding to 0.78% of the national territory.